PEMINDAHAN HAK MILIK ATAS TANAH YANG BELUM BERSERTIPIKAT MELALUI JUAL BELI YANG BERKEPASTIAN HUKUM - Muh Bangsu (JURNAL LEGISIA, 2022)
The awareness of the Indonesian people in terms of documentation of ownership of land, is still low, especially in villages, many lands owned by residents do not have a certificate of property rights, even though it is known that a certificate of property rights to land is mandatory for every landowner, as the highest and strongest recognition of land ownership. There is land hak milik that has not been registered, meaning that the Land Title has not been issued a certificate as a proof of rights by the District / City Land Office, or still marked with proof of Petuk Pajak Bumi / Landrente, Girik, Pipil, Ketitir issued certificates as proof of rights by the District / City Land Office, Verponding Indonesia, which is now replaced with a Leter C Quote. Leter C quote is published by the Village Head/Kelurahan. Based on the above issue, whether the sale and purchase of land hak milik marked with evidence of Land Tax Petuk must be made with a PPAT deed and what are the obligations of the purchaser of the land hak milik marked evidence petuk pajak bumi so that the land purchased can be listed Yes, this research uses normative methods with a statutory approach, and various literature related to the problems described after going through the study of problems with undand-laws that are connected with legal theory to strengthen the analysis of reaching conclusions. The validity of the sale and purchase of title to land marked with evidence of petuk pajak bumi is determined by the fulfillment of material conditions for the seller of the land and the purchaser of the land. The material condition for the seller of the land is that the seller is entitled and authorized to sell title to the land, the registration of the land is carried out an affirmation of conversion (recognition of rights). In the registration of the land, a deed of sale and purchase of Property Rights on land marked with proof of Land Tax Petukmade by the authorized Land Deed Making Officer (PPAT) is included.